2020
DOI: 10.1037/apl0000436
|View full text |Cite
|
Sign up to set email alerts
|

Abusive supervision, thwarted belongingness, and workplace safety: A group engagement perspective.

Abstract: Drawing from the group engagement model of justice, we examine how and when higher abusive supervision relates to fewer safety behaviors and worse safety performance. In Study 1, a 2-wave survey study of 468 manufacturing technicians, we found that belongingness need satisfaction mediated the negative relationship between abusive supervision and safety behavior. In Study 2, a multiwave survey study of 589 airline pilots, we found that safety behavior mediated the adverse relationship between abusive supervisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 89 publications
3
48
0
Order By: Relevance
“…Previous studies on leadership and group dynamics highlighted the impact of positive leadership behavior on group outcomes [54] but paid less attention to the relationship between negative leadership behavior and group outcomes. Even less research has probed the impact of destructive leadership such as abusive supervision and workplace bullying on group outcomes [2,55]. Consequently, the influence of negative leadership on such group outcomes as supervision incivility has generally been left unexplored [2].…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Previous studies on leadership and group dynamics highlighted the impact of positive leadership behavior on group outcomes [54] but paid less attention to the relationship between negative leadership behavior and group outcomes. Even less research has probed the impact of destructive leadership such as abusive supervision and workplace bullying on group outcomes [2,55]. Consequently, the influence of negative leadership on such group outcomes as supervision incivility has generally been left unexplored [2].…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Likewise, the study pointed out that there is a close relationship with interpersonal and happiness mood. Individuals with positive emotions have a higher sense of happiness and interpersonal relationships, and are more willing to invest more resources in work, while individuals with negative emotions have lower sense of happiness and interpersonal relationships, and are unwilling to invest more work resources [15,16]. Thus, negative emotions had a significantly negative predictive effect on employee engagement, while positive emotions did not.…”
Section: The Mediating Effect Of Positive and Negative Emotionsmentioning
confidence: 99%
“…From a challenging perspective, some studies believe that job insecurity has a positive impact on engagement. For example, some scholars found job insecurity has a significant positive impact on engagement by a large number of interviews and surveys [15,16]. Therefore, the impact of job insecurity on employee engagement needs to be further verified.…”
Section: Introductionmentioning
confidence: 99%
“…The second pathway was from fairness of supervisor to support of supervisor for safety and compliance with safety. A positive influence was found for safety support of management on safety support of supervisor (Yang, Zheng et al, 2019). It was concluded that safety conditions are influenced by management.…”
Section: Supervisors Safety Practicesmentioning
confidence: 89%